2015
DOI: 10.1038/srep16030
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between weight change and risk of hip fracture: meta-analysis of prospective studies

Abstract: The relationship between weight change and risk of hip fracture is still controversial. We searched PubMed and Embase for studies on weight change and risk of hip fracture. Eight prospective studies were included. The weight loss studies included 85592 participants with 1374 hip fractures, and the weight gain studies included 80768 participants with 732 hip fractures. Weight loss is more likely a risk factor of hip fracture, with an adjusted RR (Relative Risk) (95% CI) of 1.84 (1.45, 2.33). In contrast, weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 49 publications
0
19
0
3
Order By: Relevance
“…Body weight correlated positively with the bone mineral density of the proximal femur in postmenopausal women aged 75 years and older [29]. Weight loss is shown to be a risk factor of hip fracture in a recent systematic review and meta-analysis paper [30]. Among the six included studies, five used the CHS criteria or LASA frailty instrument, both of which contain weight loss as a criterion.…”
Section: Discussionmentioning
confidence: 97%
“…Body weight correlated positively with the bone mineral density of the proximal femur in postmenopausal women aged 75 years and older [29]. Weight loss is shown to be a risk factor of hip fracture in a recent systematic review and meta-analysis paper [30]. Among the six included studies, five used the CHS criteria or LASA frailty instrument, both of which contain weight loss as a criterion.…”
Section: Discussionmentioning
confidence: 97%
“…Although an emerging area, our findings are in general agreement with other studies monitoring legacy effects of WL on bone health, and suggest that declining bone mass may persist after WL ceases, or reverses. (13)(14)(15)(16)(17) Large prospective studies consistently show that WL is associated with higher hip fracture risk in older adults, (57) even among those who are overweight or obese. (7) Importantly, newly published results from the Look AHEAD study (the only RCT, to our knowledge, which has examined the effect of longterm intentional WL on fracture incidence in overweight and obese adults) confirms that 6% to 9% WL achieved and maintained over nearly a decade increases frailty fracture by 39%, (58) with concomitant loss in BMD (59,60) -although it is worth noting that the overall fracture incidence was the same for those randomized to WL versus education control.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that the number of hip fracture in the world will increase from 1.66 million in 1990 to 6.26 million by 2050 [2]. There is a demonstrated research show that approximately 19% of all hip fractures were attributed to cigarette smoking, and the relative risk (RR) for current smokers comparing with never smokers was consistently higher in male than in female [3].…”
Section: Introductionmentioning
confidence: 99%